2006
DOI: 10.1016/j.jet.2005.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Internet auctions with many traders

Abstract: A multi-unit auction environment similar to Ebay is studied. Sellers who wish to sell a single unit of a homogenous good set reserve prices for their own independently run auctions. Buyers who hope to acquire a single unit bid as often as they like in a dynamic second price auction. When the number of buyers and sellers is large but finite, there is a Bayesian equilibrium for this completely decentalized trading procedure in which the ex post efficient set of trades occurs at a uniform trading price. Remarkabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
62
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(64 citation statements)
references
References 22 publications
1
62
1
Order By: Relevance
“…Further, the notion of information transfer across multiple concurrent competing auctions that might alter bidder behavior is found in some recent works. Anwar et al (2006) found cross bidding activities in simultaneous auction settings and Peters and Severinov (2006) provided a theoretical explanation about potential equilibrium across multiple competing auctions. Zeithammer (2006) analyzed the impact of knowledge about future auctions on the bidding strategy in the current auction in sequential setting.…”
Section: Prior Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the notion of information transfer across multiple concurrent competing auctions that might alter bidder behavior is found in some recent works. Anwar et al (2006) found cross bidding activities in simultaneous auction settings and Peters and Severinov (2006) provided a theoretical explanation about potential equilibrium across multiple competing auctions. Zeithammer (2006) analyzed the impact of knowledge about future auctions on the bidding strategy in the current auction in sequential setting.…”
Section: Prior Workmentioning
confidence: 99%
“…While some researchers studied the interdependency of multiple auctions in the context of cross bidding activities (Anwar et al 2006;Peters and Severinov 2006) and price anomaly (Ashenfelter 1989;McAfee and Vincent 1993;Engelbrecht-Wiggans and Kahn 1999) in simultaneous and sequential settings, a more general and comprehensive term, overlapping auctions, has recently been formalized (Bapna et al 2009). According to Bapna et al (2009), when two or more auctions share a non-zero time span-before the close of one auction another starts, they are overlapping auctions.…”
Section: Introductionmentioning
confidence: 99%
“…Peters and Severinov [18] show the existence of a Bayesian equilibrium in a setting of homogeneous items with a large number of buyers and sellers.…”
Section: Remark 2 (Strategic Behavior: Single Unit Demand)mentioning
confidence: 99%
“…SeePeters and Severinov (2001) for a a model that allows buyers to switch to another auction if outbid.…”
mentioning
confidence: 99%
“…Unfortunately, however, our model of competition does not seem appropriate for the Internet, where buyers can move to another auction if outbid (seePeters and Severinov (2001) for a more appropriate model).6 SeeLinial (1992) for a thorough review of computer science techniques that have game-theoretic implications.7 As is common in the early auction literature we use the term "Dutch Auction" for a descending clock auction. Some internet auction sites use the term "Dutch auctions" to describe multi-unit auctions or versions of the English auction.…”
mentioning
confidence: 99%